2015
DOI: 10.4103/0366-6999.161361
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of 224 Patients with Hypertriglyceridemia Pancreatitis

Abstract: Background:Hypertriglyceridemia (HTG) is the most common etiology of acute pancreatitis (AP) after alcohol and gallstone-induced disease. Elevation of serum triglyceride (TG) levels to ≥1000 mg/dl in a patient with AP strongly indicates HTG as the cause. The absolute risk of pancreatitis based on serum TG ≤1000 mg/dl has not been clearly defined. The aims of this study were to address the role of elevated TG levels between 500 and 1000 mg/dl in the clinical course of HTG pancreatitis (HTGP); and assess the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 27 publications
4
43
1
5
Order By: Relevance
“…we observed that AP severity was positively associated with serum triglyceride levels rather than the serum amylase levels (Fig. S5) and this was consistent with the clinical characteristics of HTG - AP1819. In view of the most remarkable injury of mice AP induced by high dose P-407, hence, we adopted the dose (0.5 g/kg) as the follow-up experiment research dose.…”
Section: Resultssupporting
confidence: 75%
“…we observed that AP severity was positively associated with serum triglyceride levels rather than the serum amylase levels (Fig. S5) and this was consistent with the clinical characteristics of HTG - AP1819. In view of the most remarkable injury of mice AP induced by high dose P-407, hence, we adopted the dose (0.5 g/kg) as the follow-up experiment research dose.…”
Section: Resultssupporting
confidence: 75%
“…23 In this study, patients with AP who had a TG level of ≥11.3 mmol/L (1000 mg/dL) or between 5.65 and 11.3 mmol/L (500-1000 mg/dL) accompanied by lactescent serum in the absence of other obvious aetiology of pancreatitis were diagnosed with HTG-induced AP according to the Chinese guideline for AP and study of HTG-AP. 11,24,25 In this study, a severe course of disease with higher TG levels on admission was observed among patients with HTG-AP. Findings from the present study support and extend previous work in this area.…”
Section: Discussionmentioning
confidence: 52%
“…A retrospective study of 224 patients with HTG-AP showed that incidence of SAP in patients with TG levels >11.3 mmol/L (1000 mg/dL) was higher as compared with patients with TG levels of 5.65-11.3 mmol/L (500-1000 mg/dL). 24 However, not all studies have shown a consistent difference in the clinical course by the level of serum TG. 19,20 The present study provides further support for a significant trend towards severe AP 17 In view of the relationship between admission TG levels and disease severity, it is important for clinicians to identify these high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations